Development of monotheism motif science teaching materials for early children - Amelia, Lina; Fitria, Miftahul; Shalihah, R.A Marathun; Maisarah, Siti; Santika, Nova; Ulhanisa, Ririn (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
The research aims to develop science teaching materials with a monotheism motif for young children. It is in the form of an electronic book in the book creator application. The type of research is R&D with the ADDIE model-data collection techniques through expert test questionnaires and product feasibility questionnaires by users. The development process starts with a research needs analysis, which produces the basic concepts for book development and book feasibility instruments. The teaching material design process produces a book writing and appearance design, activity process design, teaching material design, media, teaching material evaluation instrument design, and book suitability instrument design. The development stage produces an initial draft of the book. The implementation stage produces a book draft ready to be published and distributed to users. The feasibility test results were found to be appropriate in terms of material and language, with an average indicator value of 3.7, categorized as appropriate with slight revisions. Judging from the children's understanding of the material, they received an average score of 82.03, which is considered high. Judging from the suitability of users with 11 question items on a scale of 5, the average was 4, which means the book can be disseminated with a little revision. The limitation of this research is that the product produced cannot be used directly by children, so the effect of developing this teaching material for children is less productive. because the book is intended for educators and parents.